Antidepressant-like effects of Xiaochaihutang in a neuroendocrine mouse model of anxiety/depression. (24th December 2016) - Zhang, Kuo; Yang, Jingyu; Wang, Fang; Pan, Xing; Liu, Jian; Wang, Lijuan; Su, Guangyue; Ma, Jie; Dong, Yingxu; Xiong, Zhili; Wu, Chunfu
Abstract: Ethnopharmacological relevance: Hyperactivity of hypothalamic-pituitary-adrenal (HPA) axis is often observed in the pathophysiology of depression. Antidepressant therapy can restore hippocampal neurogenesis to rescue the HPA axis regulation defects. Xiaochaihutang (XCHT), a famous Chinese herbal formula, has been used clinically in depressive disorders in China. Our previous studies have demonstrated XCHT improved depressive-like behaviors in chronic unpredictable mild stress rat, but the underlying mechanisms of XCHT on hippocampal neurogenesis and the HPA axis were still unclear. Materials and methods: We used chronic corticosterone (CORT)-induced mouse model of anxiety/depression to investigate antidepressant-like effects of XCHT by several physical and behavioral testing, including body weight, coat state, open field test, elevated plus maze, tail suspension test and forced swimming test. The integrity of negative feedback function on HPA axis was assessed by the dexamethasone (DEX) suppression test. In addition, Ki-67 and doublecortin (DCX) were performed to assess hippocampal cell proliferation and neurogenesis by immunohistochemistry. Chemical profile of active constituents in brain after oral administration of XCHT was revealed by ultra performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). Results: Our results showed that oral administration of XCHT (2.3, 7 and 21 g/kg) for 30 days remarkably normalized chronic CORT-induced the slowness in weight gain, the deterioration in coat state, the escape behavior in open field test and elevated plus maze, and the increase of immobility time in tail suspension test and forced swimming test. Moreover, XCHT significantly reversed chronic CORT-induced the reduction of DEX-induced plasma corticosterone/c-Fos suppression and Ki-67/DCX positive cells. Finally, a total 13 potential active constituents in brain were identified by UPLC-MS/MS after oral administration of XCHT, including 10 prototype components and 3 metabolites. Conclusions: Our findings showed that XCHT could remarkably alleviate chronic CORT-induced anxiety/depression-like behaviors, which were probably attribute to promoting hippocampal neurogenesis and remodeling the integrity of the negative feedback loop on HPA axis. The constituents identified in brain might contribute to understanding the therapeutic basis of XCHT on depression. Graphical abstract: